Upacara Adat Gawai Suku Dayak Kalbar sebagai Kearifan Lokal dan Pembentuk Nilai Solidaritas - Rengat, Irenius Selsus; Ronaldo, Paskalis; Hexano, Sirilus Anantha Deva (Fakultas Ilmu Budaya, Universitas Jambi, 2022)
The traditional ceremony of the Dayak’s Gawai is a tradition passed down from generation to generation which is intended as an greeting to Jubata or The Creator. However, on the other hand, this gadget tradition forms the value of local wisdom and the value of solidarity. This article focuses on local wisdom that exists in West Kalimantan, especially the Gawai traditional ceremony of the Dayak tribe as forming the value of solidarity. The main discussion that the author wants to raise is the traditional Dayak’s Gawai ceremony being a good opportunity to pass on the local wisdom of the Dayak tribe, introduce Dayak culture to others and take the value of solidarity from the Dayak’s Gawai ceremony, observing as well as collecting data from various existing sources. The purpose of this paper is to dig deeper into the traditions that exist in the Dayak tribe, especially the Gawai Dayak tribe. The thing that was found after the author collected from various sources was that the Dayak tribe had many traditions handed down by their ancestors, especially here, namely the traditional Dayak’s Gawai ceremony as a form of solidarity value.